Precessional effects in the linear dynamic susceptibility of uniaxial superparamagnets: Dependence of the ac response on the dissipation parameter - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH (American Physical Society, 2001)
It is shown that the low-frequency relaxation spectrum of the linear dynamic susceptibility of uniaxial single domain particles with a uniform magnetic field applied at an oblique angle to the easy axis can be used to deduce the value of the damping constant.
PUBLISHED
Keywords: Electronic & Electrical Engineering